Bacterial and protist community changes during a phytoplankton bloom. (15th October 2015) - Pearman, John K.; Casas, Laura; Merle, Tony; Michell, Craig; Irigoien, Xabier
Abstract: The present study aims to characterize the change in the composition and structure of the bacterial and microzooplankton planktonic communities in relation to the phytoplankton community composition during a bloom. High‐throughput amplicon sequencing of regions of the 16S and 18S rRNA gene was undertaken on samples collected during a 20 day (d) mesocosm experiment incorporating two different nutrient addition treatments [Nitrate and Phosphate (NPc) and Nitrate, Phosphate and Silicate (NPSc)] as well as a control. This approach allowed us to discriminate the changes in species composition across a broad range of phylogenetic groups using a common taxonomic level. Diatoms dominated the bloom in the NPSc treatment while dinoflagellates were the dominant phytoplankton in the control and NPc treatment. Network correlations highlighted significant interactions between OTUs within each treatment including changes in the composition of Paraphysomonas OTUs when the dominant Chaetoceros OTU switched. The microzooplankton community composition responded to changes in the phytoplankton composition while the prokaryotic community responded more to changes in ammonia concentration.